COMPUTED TOMOGRAPHIC CHARACTERISTICS OF EOSINOPHILIC PULMONARY GRANULOMATOSIS IN FIVE DOGS. Issue 1 (17th September 2013) - Fina, Caroline; Vignoli, Massimo; Terragni, Rossella; Rossi, Federica; Wisner, Erik; Saunders, Jimmy H.
<x xml:space="preserve">Abstract</x> Canine pulmonary eosinophilic granulomatosis is a rare inflammatory pulmonary disease characterized by formation of eosinophilic granulomas that tend to obliterate the normal pulmonary architecture. The purpose of this retrospective study was to describe the CT characteristics of confirmed idiopathic pulmonary eosinophilic granulomatosis in a group of dogs. Five dogs met inclusion criteria. All patients were young adult dogs of variable breeds. No dog had concurrent occult heartworm disease. Computed tomographic characteristics most commonly included pulmonary masses and nodules of variable size, and lesions were most commonly located in the caudal lung lobes. Four dogs had large pulmonary masses with or without additional nodules and one dog had nodular lesions disseminated throughout the entire lung parenchyma. All large eosinophilic granulomas were smoothly margined, heterogeneous pulmonary masses displaying heterogeneous contrast enhancement. A honeycomb‐like enhancement pattern was observed in all but one mass and consisted of multiple hyperattenuating rims delineating central hypoattenuating areas, suggestive of bronchiectatic lung with peripheral enhancing airway walls and fluid‐filled, necrotic bronchial lumen. One dog had evidence of tracheobronchial lymphadenopathy. Findings indicated that canine eosinophilic pulmonary granulomatosis should be included as a differential diagnosis for dogs with CT characteristics of multiple pulmonary masses and/or nodules in caudal lung lobes, and a honeycomb‐like enhancement pattern in masses after intravenous administration of iodinated contrast medium.